The relationship between culture, commitment and performance in a South African electricity utility - Pittorino, Leonardo Andres (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
The Electricity Distribution Industry (EDI) in South Africa is in the process of restructuring into six Regional Electricity Distributors (REDs). This would entail the merging of the national electricity utility, Eskom Distribution with municipalities to consolidate skills and to improve on efficiencies. This integration would involve the assimilation of not only physical assets but also various organisational cultures into a separate organisation responsible for supplying electricity services within its designated geographical area. A separate challenge facing Eskom is an intensive capital expansion program to increase generation capacity which will require a committed workforce to execute. Organisational culture has been regarded as leading to greater productivity and generating commitment to the values and philosophies of the organisation. The purpose of the research was to determine whether there was a significant relationship between the organisational culture, organisational commitment and employee performance in Eskom Southern Region. In order to achieve this purpose a survey was undertaken (N=83) which measured perceptions regarding the existing organisational culture, preferred organisational culture as well as organisational commitment. Performance rating scores were linked to each respondent and were obtained from the performance management process of Eskom Southern Region. The main findings of this research can be summarised as follows: "¢ The dominant existing organisational culture in Eskom Southern Region is the power culture, while the dominant preferred organisational culture is the achievement culture. "¢ There is a significant organisational culture gap between the existing and the preferred organisational culture in Eskom Southern Region. "¢ The dominant organisational commitment within Eskom Southern Region is affective commitment together with normative commitment. "¢ The findings related to the employee performance include: o A slight but significant negative relationship was measured between the existing achievement culture and employee performance. o No significant relationships were measured between the preferred cultures and employee performance. o No significant relationships were measured between the organisational commitment scales and employee performance. "¢ The findings pertaining to the relationship between organisational culture and organisational commitment can be stated as follows: o A significant positive linear relationship between the existing achievement culture and affective commitment was measured. A strong, significant negative linear relationship between the existing power culture and the affective commitment was also measured. o No significant relationships were measured between the preferred organisational cultures and organisational commitment. o The organisational culture gap has a significant effect on the organisational commitment of employees. "¢ The findings pertaining to the relationship between the biographical variables and the organisational culture, organisational commitment and employee performance can be stated as follows: o There exists a strong significant relationship between the years of service and the existing organisational culture scales. o No significant relationships exist between the preferred organisational culture scales and any of the biographical variables. There was a common agreement across all respondents on the preferred organisational culture. o A significant relationship was found between organisational commitment and the number of people supervised. o A slight but significant positive linear relationship between the age of respondents and employee performance ratings was measured. It can therefore be concluded that the type of organisational culture has a significant impact on the level of affective commitment of the employees within Eskom Southern Region. No significant positive relationship was found between organisational commitment and organisational performance in Eskom Southern Region.
Keywords: Eskom (Firm) -- Employees; South Africa -- Electricity Supply Commission; Corporate culture -- South Africa -- Research; Management -- South Africa -- Research; Organization -- South Africa -- Research; Employees -- South Africa -- Research